Peran Kegiatan Ekstrakurikuler dalam Membangun Budaya Multikulturalisme di Pondok Pesantren - Masnor Maltufah; Faizun Najah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Perception refers Perception is an individual's way of viewing a situation, shaped by their experiences, environment, and values. Communication strategy is the planning and management done to achieve a particular goal. This study focuses on three research questions: 1. What is the perception of outstanding students in developing communication skills? 2. What is the strategy of outstanding students in developing communication skills? 3. What are the opportunities and challenges faced by outstanding students in building communication skills? The study uses a descriptive qualitative approach. The data collection techniques employed include interviews, observation, and documentation. The results indicate that the perception of outstanding students in developing communication skills includes: 1. Learning through practice, and 2. Having both introverted and extroverted traits. The strategies of outstanding students in developing communication skills include: 1. Recognizing the audience, 2. Non-verbal communication, 3. Joining interest groups, 4. Applying the